Genome-wide identification, characterization and expression analysis of the bZIP transcription factors in garlic (Allium sativum L.) - He, Shutao; Xu, Sen; He, Zhengjie; Hao, Xiaomeng (Frontiers in Plant Science, 2024)
Introduction The bZIP genes (bZIPs) are essential in numerous biological processes, including development and stress responses. Despite extensive research on bZIPs in many plants, a comprehensive genome-wide analysis of bZIPs in garlic has yet to be undertaken. Methods In this study, we identified and classified 64 AsbZIP genes (AsbZIPs) into 10 subfamilies. A systematic analysis of the evolutionary characteristics of these AsbZIPs, including chromosome location, gene structure, conserved motifs, and gene duplication, was conducted. Furthermore, we also examined the nucleotide diversity, cis-acting elements, and expression profiles of AsbZIPs in various tissues and under different abiotic stresses and hormone treatments. Results and Discussion Our findings revealed that gene replication plays a crucial role in the expansion of AsbZIPs, with a minor genetic bottleneck observed during domestication. Moreover, the identification of cis-acting elements suggested potential associations of AsbZIPs with garlic development, hormone, and stress responses. Several AsbZIPs exhibited tissue-preferential and stress/hormone-responsive expression patterns. Additionally, Asa7G01972 and Asa7G01379 were notably differentially expressed under various stresses and hormone treatments. Subsequent yeast two-hybridization and yeast induction experiments validated their interactions with Asa1G01577, a homologue of ABI5, reinforcing their importance in hormone and abiotic stress responses. This study unveiled the characteristics of the AsbZIP superfamily and lays a solid foundation for further functional analysis of AsbZIP in garlic.